ECONOMIC EFFICIENCY OF PRODUCTION AND COMMERCIAL ACTIVITIES OF AGRICULTURAL ENTERPRISES: CURRENT TRENDS AND DIRECTIONS FOR ITS IMPROVEMENT - KALINICHENKO, Sergiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to assessing the efficiency of production and commercial activities of agricultural enterprises and substantiating directions for their improvement under current operating conditions. This article aims to provide a comprehensive assessment of the efficiency of production and commercial activities of Ukrainian agricultural enterprises and to identify directions for their improvement. The principles of assessing the efficiency of production and commercial activities of agricultural enterprises are considered in the context of transformational changes occurring in the national farming sector. The production of crop and livestock products is analyzed, highlighting the dominance of crop production and the deepening disproportions between various types of agricultural production. It was found that the gross value added of the farm sector increased by 2.5 times over the study period, while the net value added increased by 2.4 times, indicating growth in productivity and modernization of the technical and technological base of enterprises. The livestock sector exhibited a steady decline during the analyzed period. The reduction in the production of milk, eggs, wool, and other livestock products indicates a systemic crisis in the industry, caused by low investment attractiveness, deterioration of the resource base, and insufficient renewal of fixed assets. Research on production by farm categories showed that agricultural enterprises are increasingly dominating the production structure. The study allowed identifying directions for increasing the efficiency of production and commercial activities in the agricultural sector: improving the effectiveness of production resource use, creating and increasing added value, increasing production profitability, strengthening the financial stability and investment capacity of farming enterprises, developing production and commercial integration, structural optimization of sectoral development within enterprises, growth of human capital and managerial competence, and innovation-technological modernization. Overall, it is concluded that the efficiency of commercial activities is determined by the enterprise’s ability to diversify sales markets, improve contractual relations with traders, optimize logistics costs, and ensure growth in sales volumes.